2020
DOI: 10.1039/d0sc04040a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous manifestation of metallic conductivity and single-molecule magnetism in a layered molecule-based compound

Abstract: Single-molecule magnets (SMMs) show superparamagnetic behaviour below blocking temperature at the molecular scale, so they exhibit large magnetic density compared to the conventional magnets. Combining SMMs and molecular conductors in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…20 In fact, as one the most studied mononuclear cobalt systems, the magneto-structural correlations on the distorted tetrahedral mononuclear cobalt complexes have been well studied experimentally and computationally. 20,[35][36][37][38][39][40][41][54][55][56] Generally, a smaller N-Co-N bite angle will result in a larger zero-field splitting. One of the recent studies revealed the significant non-linear dependency of the d-orbital splitting on the N-Co-N bite angle.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…20 In fact, as one the most studied mononuclear cobalt systems, the magneto-structural correlations on the distorted tetrahedral mononuclear cobalt complexes have been well studied experimentally and computationally. 20,[35][36][37][38][39][40][41][54][55][56] Generally, a smaller N-Co-N bite angle will result in a larger zero-field splitting. One of the recent studies revealed the significant non-linear dependency of the d-orbital splitting on the N-Co-N bite angle.…”
Section: Papermentioning
confidence: 99%
“…33,34 Following these lines, we further turned our attention to a tetrahedral mononuclear complex (HNEt 3 ) 2 [Co ( pdms) 2 ] (H 2 pdms = 1,2-bis(methanesulfonamide)benzene, Scheme 1), which possesses the highest reported effective energy barrier (213 cm −1 ) among the air-stable transitionmetal SIMs. 20 Then, this complex has been used as a great magnetic building unit for the development of novel magnetic conductors [35][36][37] and as a molecular model for theoretical investigation, 38,39 and inspired the construction of a radicalbridged dimeric Co II SMM 40 and similar Co II SIMs. 41 Encouraged by these interesting works, herein we found that the dianionic mononuclear complex [Co( pdms) 2 ] 2− is liable to form the stable neutral [Co( pdms)] species in the presence of nitrogen-containing organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high number of spins in the ground state and strong uniaxial magnetic moments, lanthanoid-based SMMs have been shown to display high performances, such as high energy barriers ( U ) and long relaxation times (τ). Our group has focused on the cooperation of SMMs and electrical conductivities (σ) in one system, that is, a new class of nanomaterials called conductive SMMs, by using SMMs and organic conductors, such as bis­(ethylenedithio)­tetrathiafulvalene (BEDT-TTF, abbreviated as ET) and bis­(ethylenedioxy)­tetrathiafulvalene (BEDO-TTF, or BO). Yagubskii et al and our group have independently reported several conductive SMMs with Re 4+ , Mn 2+/3+ , and Co 2+ transition metal ions and ET, BO, and M­(dmit) 2 conductors (dmit = 4,5-dimercapto-1,3-dithiole-2-dithione), some of which exhibit metallic SMM properties in the same temperature range. However, in comparison to transition metal-based SMMs, there are few reports on 4f-based conductive SMMs. We first reported the electrocrystallization of a Dy 3+ -based magnetic chain and ET molecules to afford semiconductive SMM compounds .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the first conductive field-induced SMM was synthesized-(BEDO) 4[ReF6]•6H2O-in which conductivity and single-molecule magnetism coexist in the same temperature range [16]. More recently, another BEDO salt has been synthesized with a monomolecular magnet [Co(pdms)] 2-as a counterion, which also shows the coexistence of conductivity and monomolecular magnetism up to 11 K [17].…”
Section: Introductionmentioning
confidence: 99%